PREVALENCE AND INDICATION AND OUTCOME OF CESAREAN SECTION IN JUGAL HOSPITAL, HARARI REGIONAL STATE, ETHIOPIA, 2019: A RETROSPECTIVE STUDY - Arif Hussen Jamie (Public Health of Indonesia)
Background: Rising rates of cesarean delivery is becoming a concern to developing countries. Though cesarean section is a lifesaving surgical intervention, the rise in rates has resulted in significant health problems of mothers and newborns.